2023
DOI: 10.1101/2023.10.24.563888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Keratin 6a attenuates Toll-like receptor-triggered proinflammatory response in corneal epithelial cells by suppressing ELKS/IKKε-dependent activation of NF-κB

Jonathan K. Chan,
Yan Sun,
Anand Bhushan
et al.

Abstract: The corneal epithelium at the ocular surface is constantly exposed to the environment and represents the first line of defense against infection, mechanical injury or chemical irritation. Through TLR-mediated recognition of pathogen- and damage-associated molecular patterns, it engages in direct antimicrobial responses and alerts the immune system on intruder and tissue damage by secreting pro-inflammatory and chemotactic cytokines that promote immune cell infiltration. How the corneal epithelium downregulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 87 publications
2
1
0
Order By: Relevance
“…Our investigation started with multiplex assays and conventional ELISA measuring cytokine secretion from hTCEpi cells untreated or treated with cell-free bacterial culture supernatants containing a mixture of inflammatory Toll-like receptor ligands. As multiple cytokines released from K6a-KD cells are upregulated as compared to WT cells, these findings are consistent with our recent report, which has shown that K6a knockdown causes increased NF-kB activation and cytokine expression in hTCEpi cells and mouse corneal epithelium challenged with purified LPS and LTA, and that mechanistically, ELKS-interacting K6a is a newfound negative regulator of non-canonical NF-kB signaling for preventing excessive expression of proinflammatory cytokines and chemokines at the transcriptional level 27 . In this study, K6a interactome analysis has identified Sec16A and showed various autophagy and secretory pathways enriched in hTCEpi cells; so silencing K6a has led to elevated LC3-II level (lysate protein and cytoplasmic puncta), whether or not the cells are stimulated with inflammatory ligands, suggesting a possible relationship between K6a, autophagy and cytokine secretion.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our investigation started with multiplex assays and conventional ELISA measuring cytokine secretion from hTCEpi cells untreated or treated with cell-free bacterial culture supernatants containing a mixture of inflammatory Toll-like receptor ligands. As multiple cytokines released from K6a-KD cells are upregulated as compared to WT cells, these findings are consistent with our recent report, which has shown that K6a knockdown causes increased NF-kB activation and cytokine expression in hTCEpi cells and mouse corneal epithelium challenged with purified LPS and LTA, and that mechanistically, ELKS-interacting K6a is a newfound negative regulator of non-canonical NF-kB signaling for preventing excessive expression of proinflammatory cytokines and chemokines at the transcriptional level 27 . In this study, K6a interactome analysis has identified Sec16A and showed various autophagy and secretory pathways enriched in hTCEpi cells; so silencing K6a has led to elevated LC3-II level (lysate protein and cytoplasmic puncta), whether or not the cells are stimulated with inflammatory ligands, suggesting a possible relationship between K6a, autophagy and cytokine secretion.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, upon stimulation by 20% PAO1 culture supernatant, K6a-KD cells also secreted higher levels of IL-1a, IL-6, IL-8, GROa/CXCL-1 as compared to wild type cells (Figure 1A). Next, we validated some of these findings by traditional ELISA (Figure 1B), which was in line with our recent findings 27 . These results indicated that K6a in corneal epithelial cells negatively regulates secreted levels of proinflammatory mediators.…”
Section: Endogenous K6a Suppresses Proinflammatory Cytokine and Chemo...supporting
confidence: 90%
See 1 more Smart Citation